PENGARUH PENGUMUMAN DIVIDEN TERHADAP PERUBAHAN HARGA SAHAM (RETURN) SEBELUM DAN SESUDAH EX-DIVIDEND DATE DI BURSA EFEK INDONESIA (BEI) - SOFIYULLAH SOFIYULLAH; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to study how to announce dividends on stock prices on the Indonesia Stock Exchange, using a sample of LQ45 companies which are divided into 22 companies that distribute up dividends and 23 companies that distribute up dividends. The research period is 15 days before the announcement and 15 days are announced. The method used is an event study to see stock price movements, with abnormal returns when the dividend announcement rises and falls after the ex-dividend date. The results of this study indicate that dividend announcements go up investors give a negative reaction on the contrary on dividend announcements down investors positively assess when the company makes dividend announcements after the ex-dividend date.Keywords: Dividend Announcement; Stock Price; Abnormal Return